Ultrasound-assisted extraction (UAE) of phenolic compounds from different Brosimum alicastrum tissues - Negrón-Diaz, Andrea Carolina; Aguilar-Piloto, Gustavo; Moo-Huchin, Victor Manuel; Delgadillo-Díaz, Mariana; Sauri-Duch, Enrique (Ecosistemas y Recursos Agropecuarios, 2023)
The effect of solvent-to-tissue ratio (STR) and lyophilized tissue type (LT) in UAE on the content of total phenolic compounds (TPC) and extraction yield (EY) of B. alicastrum was evaluated. Phenolic compounds from the fruit peel, seed skin, seed and lyophilized leaf were extracted with ethanol-distilled water (1:1, v/v) in an ultrasonic bath varying STR between 20 and 60 mL g‒1 at 30 min, 30 °C and 100 % amplitude. The response variables evaluated were: TPC and EY. The main effects (LT and STR) and their interaction showed a significant influence on polyphenol UAE. The higher the STR, the higher the TPC content. When comparing LT, seed and fruit peel exhibited higher TPC and EY values, respectively. At a STR value of 60 mL g‒1 the UAE of phenolic compounds of the analyzed tissues improved.